PERSPEKTIF QURAISH SHIHAB TENTANG PENDIDIKAN ISLAM ERA MODERN - Yesi Ulandari; Wedra Aprison (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This research discusses the importance of the role of Islamic education in the modern era. According to Quraish Shihab, achieving the perfect quality of education does not only require the role of educators and students, but more than that, it must pay attention to all things, both personnel and other roles that allow potential in developing Islamic education. Quraish Shihab wants the concept of Islamic education to be based on the Quran, therefore the concept of Islamic education must be taken from Islamic sources, one of which is the Quran, Quraish Shihab calls it Quranic education. This research can be said to be a character study, which is one type of qualitative research. The nature of a character study is an in-depth, systematic, critical study of a character's history, original ideas or ideas, and the socio-historical context surrounding the character being studied. This type of research is included in qualitative research (library research) which examines a theoretical and in-depth study so that conclusions will be obtained. Based on the analysis of the results of research conducted on the concept of Islamic education in the perspective of Quraish Shihab, there are several things that are concluded as follows: First, Quraish Shihab says that in the Qur'an there are aspects that include Islamic education, namely: the purpose of Islamic education, the method of Islamic education, the nature of Islamic education, and the material of Islamic education. Second, in the context of education according to Quraish Shihab there are roles and responsibilities given to Muslim intellectuals. Third, in the elaboration of the concept of curriculum, several characteristics are needed that must be met so that the curriculum is in harmony with the values contained in the book of Allāh Swt (Al-Qur'an).